NMR- and MS-Based Untargeted Metabolomic Study of Stool and Serum Samples from Patients with Anorexia Nervosa - Tomášová, Petra; Procházková, Petra; Roubalová, Radka; Dvořák, Jiří; Tlaskalová-Hogenová, Helena; Čermáková, Martina; Pelantová, Helena; Šedivá, Blanka; Vecka, Marek; Papežová, Hana; Kuzma, Marek (Journal of proteome research, 2022)
Anorexia nervosa (AN), a pathological restriction of food intake, leads to metabolic dysregulation. We conducted a metabolomics study to reveal changes caused by AN and the effect of hospital realimentation on metabolism. Both stool and serum from patients with AN and healthy controls were analyzed by NMR and MS. Statistical analysis revealed several altered biochemical and anthropometric parameters and 50 changed metabolites, including phospholipids, acylcarnitines, amino acids, derivatives of nicotinic acid, nucleotides, and energy metabolism intermediates. Biochemical and anthropometric parameters were correlated with metabolomic data. Metabolic changes in patients with AN described in our study imply serious system disruption defects, such as the development of inflammation and oxidative stress, changed free thyroxine (fT4) and thyroid-stimulating hormone (TSH) levels, a deficit of vitamins, muscle mass breakdown, and a decrease in ketone bodies as an important source of energy for the brain and heart. Furthermore, our data indicate only a very slight improvement after treatment. However, correlations of metabolomic results with body weight, interleukin 6, tumor necrosis factor α, fT4, and TSH might entail better prognoses and treatment effectiveness in patients with better system parameter status. Data sets are deposited in MassIVE: MSV000087713, DOI: 10.25345/C57R7X.
Keywords: metabolomika; Anorexia Nervosa; thyreotropin; nuclear magnetic resonance; metabolomics; anorexia nervosa; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Thyroid Hormones; lidé; mass spectrometry; Metabolomics; mentální anorexie; Humans; hormony štítné žlázy; Thyrotropin